Some remarks on the Poisson-Nijenhuis and the Jacobi structures - Costa, J. M. Nunes da (1999)
We study the relationship between two (compatible) J acobi structures on a manifold M, using their associated homogeneous Poisson structures on lR x M, in the case where these Poisson tensors are related by a Nijenhuis tensor.